2022
DOI: 10.3390/atmos13071120
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of PM2.5 and PM10 Spatio-Temporal Distribution and Influencing Meteorological Conditions in Beijing

Abstract: PM2.5 and PM10 in the atmosphere seriously affect human health and air quality, a situation which has aroused widespread concern. In this paper, we analyze the temporal and spatial distribution of PM2.5 and PM10 concentrations from 2016 to 2021 based on real-time monitoring data. In addition, we also explore the influence of meteorological conditions on pollutants. The results show that PM2.5 and PM10 concentrations are similarly distribution in temporal and spatial from 2016 to 2021, and the average concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
(43 reference statements)
1
4
0
Order By: Relevance
“…These ingredients can accumulate in the lungs and cause allergies with increased immunoglobin E and inflammation [ 28 , 29 ]. PM 2.5 concentrations have been shown to be higher in cold weather [ 30 ], and our study also found the same trends. A previous study found that PM 2.5 was related to asthma ERVs in Taipei [ 15 ].…”
Section: Discussionsupporting
confidence: 89%
“…These ingredients can accumulate in the lungs and cause allergies with increased immunoglobin E and inflammation [ 28 , 29 ]. PM 2.5 concentrations have been shown to be higher in cold weather [ 30 ], and our study also found the same trends. A previous study found that PM 2.5 was related to asthma ERVs in Taipei [ 15 ].…”
Section: Discussionsupporting
confidence: 89%
“…Based on the baseline emission factors of various types of motor vehicles in the Technical Guidelines for the Preparation of Air Pollutant Emission Inventories for Road Motor Vehicles, localized corrections were made by investigating the meteorology, motor vehicle driving conditions, etc., in Anqing City, and simulations were carried out. The calculation method is shown in Equation (2).…”
Section: Emission Factorsmentioning
confidence: 99%
“…Vehicle exhaust and evaporation emissions are important sources of near-surface ozone and secondary particle precursors in urban and regional areas. Based on PM 2.5 source analysis results in recent years, motor vehicle pollution has gradually become the major source of haze pollution in many Chinese cities [2]. Moreover, vehicle emissions, as near-surface pollutants close to areas of human activity, present a more significant health risk than many other types of anthropogenic emissions [3].…”
Section: Introductionmentioning
confidence: 99%
“…Among the particulate matter (PM) in the air, PM 10 and PM 2.5 are highly dangerous air pollutants [60]. These particles are small enough to easily pass through the lungs and enter the bloodstream [61].…”
Section: Pollutants Concentration and Aqi Levelmentioning
confidence: 99%